Frekuensi Pernafasan Anak Penderita Asma Menggunakan Intervensi Tiup Super Bubbles dan Meniup Baling Baling Bambu - Harsismanto J; Padila Padila; Juli Andri; Muhammad Bagus Andrianto; Lussyefrida Yanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aimed to see the comparison of blowing bubbles and blowing bamboo blades to the respiratory frequency of children with asthma in the Edelweiss Room, DR. M. Yunus Bengkulu Year 2019. The research design used was a quasi-experimental research. The univariate analysis results showed that the average respiratory rate before and after doing super bubble blow therapy was in the moderate category (26.91) and after the intervention was in the medium type (25.30). The average respiratory frequency before and after blowing the bamboo propeller was moderate (26.69) and light (24.81). The bivariate analysis results showed that there was an effect of blowing bubbles on respiratory frequency in children with a value of p = 0.000, and there was an effect of blowing bamboo propellers on respiratory frequency in children with asthma with a value of p = 0.007. In conclusion, there is no difference in superbubbles blowing therapy's effectiveness by blowing bamboo propellers in children with asthma. Keywords: Bamboo Propeller, Respiratory Frequency, Blow Super bubbles